Racisms : From the Crusades to the Twentieth Century - Bethencourt, Francisco (Book collections on Project MUSE., 2013)
This book is a comprehensive history of racism, from the Crusades to the twentieth century. Demonstrating that there is not one continuous tradition of racism in the West, the author, a historian shows that racism preceded any theories of race and must be viewed within the prism and context of social hierarchies and local conditions. In this book, he argues that in its various aspects, all racism has been triggered by political projects monopolizing specific economic and social resources. He focuses on the Western world, but opens comparative views on ethnic discrimination and segregation in Asia and Africa. He looks at different forms of racism, particularly against New Christians and Moriscos in Iberia, black slaves and freedmen in colonial and postcolonial environments, Native Americans, Armenians in the Ottoman Empire, and Jews in modern Europe. Exploring instances of enslavement, forced migration, and ethnic cleansing, he reflects on genocide and the persecution of ethnicities in twentieth-century Europe and Anatolia. These cases are compared to the genocide of the Herero and Tutsi in Africa, and ethnic discrimination in Japan, China, and India. Here the author analyzes how practices of discrimination and segregation from the sixteenth to the nineteenth centuries were defended, and he systematically integrates visual culture into his investigation. -- Publisher's description.